Towards the sustainability of tourist destinations: the role of trip quality and perceived value in increasing revisit intention at Madiun Umbul Square - Hamzah Nugrohanto; Yusaq Tomo Ardianto; Mokhamad Natsir; Nanny Roedjinandari; Bambang Supriadi (Jurnal Pariwisata Pesona, 2024)
The leisure tourism industry has become highly competitive, offering tourists a multitude of travel options that influence tourists' decisions. Therefore, tourism managers must understand visitor behavior to maintain tourism destinations. The sustainability of a tourist attraction can be influenced by repeat tourist visits, which is easier to achieve than attracting new tourists. Destination managers must continue to improve the quality of products and services to increase the overall value perceived by tourists, which ultimately encourages repeat visits. This research aims to investigate the relationship between trip quality, perceived value, and revisit intention among visitors to Madiun Umbul Square. This quantitative research uses an online questionnaire distributed to visitors to Madiun Umbul Square, with samples collected through incidental sampling. A total of 125 complete questionnaire responses were used as research data and analyzed using multiple regression to ensure the relationship between variables. The results of this research reveal that trip quality, apart from having a direct impact, also indirectly influences revisit intention through perceived value. This study shows the important role of perceived value in increasing the influence of trip quality to increase revisit intention. Future research suggests that researchers can further identify key attributes that form overall perceived value, especially by ensuring visitors experience trip quality positively and include other variables in this research model by adding a satisfaction variable as an antecedent of revisit intention. Previous research recommends that quality and perceived value measurements always accompany satisfaction surveys. This is because quality and value are the main drivers of satisfaction.